The role of pH, ionic strength and monomer concentration on the terpolymerization of 2-acrylamido-2-methylpropane sulfonic acid, acrylamide and acrylic acid. (26th August 2019) - Scott, Alison J.; Duever, Thomas A.; Penlidis, Alexander
Abstract: The current study examines the effects of important factors (namely, pH, ionic strength and monomer concentration) on the terpolymerization of 2-acrylamido-2-methylpropane sulfonic acid (AMPS), acrylamide (AAm) and acrylic acid (AAc). A good understanding of how these factor levels affect terpolymerization reactivity ratios, and terpolymer composition, microstructure and molecular weight paves the way for the synthesis of custom-made polymers for specific applications. For the range of conditions studied, ionic strength has the greatest influence on reactivity ratios; results indicate that cross-over behavior exists for AMPS-based reactivity ratios. No clear correlation is observed between pH and reactivity ratio estimates (for 5 ≤ pH ≤ 9), but parameter estimation results suggest that the incorporation of acidic comonomers (AMPS and AAc) is affected by pH within this range. Finally, monomer concentration has a dominant impact on molecular weight averages, even when other factors are varied. Graphical abstract: Image 1 Highlights: pH, ionic strength and monomer concentration are all significant factors. Improved understanding of factor level effects can lead to custom-made materials. Reactivity ratios can be used to select conditions leading to desirable properties. Ionic strength has greatest effect over range studied; cross-over behavior observed.